A Study on Sleep-Pattern and Sleep Hygiene Behaviors Among School Going Adolescents in Semi Urban Coimbatore - Vinodhini Balamurugan; Saranya Rajamanickam; Sugunadevi G; Rathan Pandiyan; Kadiyala, Prathyusha; Geetha A (National Journal of Community Medicine, 2023)
Background: Sleep plays an important role in our life. Adolescents undergo several changes with puberty and have a preference for later bedtimes due to internet usage. Evidence shows that many adolescents are not obtain-ing the required amounts of sleep (8-10 hours) due to inadequate sleep practices. The objectives of this research were to study sleep-pattern among adolescents in Semi urban Coimbatore and also to determine the sleep hygiene practices among the adolescents. Methodology: This study is a school based cross-sectional study. A total of 300 adolescents from class VIII to XIIth were selected using simple random sampling. Data was collected from February to May 2018. A structured questionnaire for sleep pattern and Sleep Hygiene Index was used. Results: The adolescents’ mean sleep duration was 7.49 ± 1.12 hours on weekdays and 9.32 ± 1.55 hours on weekends. Mean Sleep Pattern Index (SPI) score was 22.48±6.9 and Mean Sleep Hygiene Index (SHI) score was 17.51±6.3 in our study. Conclusions: Majority of the adolescents had moderate scores of sleep pattern and sleep hygiene practices. Inter-ventions directed towards promoting good sleep hygiene strategies are required to improve the physical and emotional health of adolescents.